Navigating shades of social capital and trust to leverage opportunities for rural innovation. (May 2019) - King, Barbara; Fielke, Simon; Bayne, Karen; Klerkx, Laurens; Nettle, Ruth
Abstract: This paper makes a contribution to understanding the impact of relational trust, as embodied within bonding, bridging and linking social capital, on rural innovation. Using cases of multi-stakeholder groups who work together on shared problems it explores how social capital and different forms of trust (companion, competence and commitment) influence rural innovation processes. Looking at both the 'bright' and 'dark' side of social capital, our focus is on how social capital and trust constrain and enable the process of innovation. The study highlights both positive and negative effects of social capital in the context of three fixed term projects that were part of New Zealand's Primary Innovation programme (2012–2017). Our findings show that there was a unique composition of social capital and trust at the outset of each project and that dark social capital was a critical constraint in each case. Enabling innovation processes required committed and dedicated brokers who provided bridging social capital and embodied competence trust to enable participants' confidence. Such brokers are capable of recognising and managing different 'shades' of social capital and trust in pursuing desired project outcomes. A main theoretical implication of this study is that a better understanding of social capital and trust is needed to enable innovation facilitators and project managers to design and undertake fixed term rural innovation projects effectively. This is because social capital determines whether the composition of relationships within networks of actors involved in innovation projects enables innovation, or to the contrary constrains innovation. Specifically the implications and implementation of bridging social capital and competence trust are key determinants of successful innovation processes. Highlights: We examine the influence of s hades of social capital ('dark' and 'bright') on fixed term innovation processes. Our unique context is multi-stakeholder, participative, fixed term rural innovation projects. The concept of trust is 'unpacked' drawing on notions of companion, competence, and commitment trust. A key finding is that bridging social capital and competence trust are key determinants of successful innovation processes.